Analysis of droplet growth of positive and negative electrode on cold metal transfer welding of aluminum wire. (June 2022) - Lv, Xiaoqing; Wang, Zhuangzhuang; Su, Haoyang; Xu, Lianyong; Jing, Hongyang
Abstract: A method was proposed to identify the boundary between droplet and welding wire by processing the image from high-speed photography in the process of Variable Polarity Cold Metal Transfer (VP CMT). The droplet volume and its variation trend in electrode positive (EP) phase and electrode negative (EN) phase of aluminum wire with different parameters were obtained. The results indicated that the melting volume of aluminum wire exhibited a positive linear relationship with the input work of plasma phase, and the droplet increasing volume of aluminum wire in EN phase was approximately 2.2 times that of EP phase under same input work. The droplet transfer process was divided into droplet rapid growth and slow growth stage according to the droplet growth rate. The welding parameters and droplet growth property in the first cycle after the polarity switching (EN to EP, EP to EN) were different from that in the following cycle.